2017
DOI: 10.1016/j.ttbdis.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation and analysis of the Ornithodoros moubata midgut genes differentially expressed after blood feeding

Abstract: The argasid tick Ornithodoros moubata is the main vector of the African swine fever and the human relapsing fever in Africa. As part of the host-parasite-pathogen interface, the tick midgut expresses key proteins for tick survival and tick-borne pathogen transmission. Accordingly, midgut proteins are potential targets for the development of new drugs and vaccines aimed at tick control, and obtaining proteomic and transcriptomic data from the O. moubata midgut would facilitate the identification of such target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 82 publications
6
55
0
Order By: Relevance
“…Up regulated genes potentially involved in protein metabolism are listed in Table 2 and Supplementary Table 3. Protein families of proteases, such as cysteine peptidases, aspartic endopeptidases, metallopeptidases and serine peptidases were signi cantly up-regulated suggesting that the proteolytic system was active [41]. The results were quite similar with some of the transcriptome studies [31,47].…”
Section: Differential Gene Expression Pro Lessupporting
confidence: 73%
See 2 more Smart Citations
“…Up regulated genes potentially involved in protein metabolism are listed in Table 2 and Supplementary Table 3. Protein families of proteases, such as cysteine peptidases, aspartic endopeptidases, metallopeptidases and serine peptidases were signi cantly up-regulated suggesting that the proteolytic system was active [41]. The results were quite similar with some of the transcriptome studies [31,47].…”
Section: Differential Gene Expression Pro Lessupporting
confidence: 73%
“…Up to 55 unigenes on carbohydrate metabolism were differentially expressed (35 in F tick group, 9 in H tick group and 11 in M tick group), covering biological process such as carbohydrate phosphorylation, protein glycosylation, glycogen catabolic process, galactose metabolic process. The results indicated that the up-regulated unigenes encoding carbohydrate-metabolizing enzymes were similar with the genes identi ed in the transcriptomes of Ixodes ricinus [67], Haemaphysalis ava [31], Dermacentor variabilis [68], and in Argasidae of Ornithodoros moubata [41] and Ornithodoros erraticus [60]. According to the annotations, the up-regulated unigenes were associated with the metabolism and transport of several carbohydrates including glucose, fructose, mannose, galactose, maltose, idose, malate and chitin (Table 4).…”
Section: Differential Gene Expression Pro Lesmentioning
confidence: 53%
See 1 more Smart Citation
“…Through the analysis of published transcriptome data from Ornithodoros ticks, we identified ASFLIspecific RNA in O. moubata ticks from laboratory colonies from Spain (18) and Japan (19) (Figure 4 and Supplementary Tables 1 and 2), while in pertinent data from O. erraticus (20) and Ornithodoros turicata (PRJNA447876) no ASFLI-specific RNA was detected ( Figure 4). Furthermore, we examined nine porcinus ticks, we detected ASFLI-specific reads or even contigs (Figure 4, Supplementary Table 6).…”
Section: O Moubata and O Porcinus Field-collected Ticks From Africamentioning
confidence: 99%
“…ROS and RNS appear to be substantial environmental challenges for B. burgdorferi during both blood meal acquisition and during starvation in I. scapularis nymphs, as ROS‐sensitive and RNS‐sensitive B. burgdorferi strains harbouring mutations in antioxidant defence genes show poor survival compared with their wild‐type counterparts (Bourret et al, ; Eggers et al, ; Li et al, ). To the best of our knowledge, the production of ROS and RNS in Ornithodoros ticks has not been reported; however, transcriptomic and proteomic studies have identified a variety of oxidant metabolism and antioxidant defence genes expressed in soft‐bodied ticks that transmit RF Borrelia (Francischetti, Mans, et al, ; Francischetti, Meng, et al, ; Landulfo et al, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ).…”
Section: Introductionmentioning
confidence: 99%